Firm Types, Price-Setting Strategies, and Consumption-Tax Incidence - Jarkko Harju; Tuomas Kosonen; Oskar Nordström Skans (Center for Economic Studies and ifo Institute (CESifo), 2015)
Studying very detailed micro data collected around two different VAT reforms in Europe, we show that tax incidence is heavily dependent on the characteristics of the price-setting firms. The reforms generated bimodal price-change distributions; nearly all independent restaurants left prices unchanged whereas a substantial fraction of restaurants belonging to chains chose a complete passthrough. These differences cannot be explained by location, initial prices or other market-segment indicators. Instead, differences appear to arise because independent restaurants aim for (very) crude price ranges rather than fine-tuned optimized prices, whereas chains use more elaborate, coordinated pricing strategies.
Keywords: H22; H32; E31; 330; firm heterogeneity; VAT; price incidence; price setting; restaurants